Głos w sprawie partycypacji samorządu terytorialnego w podatkach państwowych - Langer, Mateusz (Kwartalnik Prawa Podatkowego, 2015)
The goal of the article is an attempt to present the alternative methods of participation in receipts from state taxes obtained by local authority in Poland. In particular, the author has devoted a lot of space to assess the theoretical assumptions underlying the two variants of these changes: diversification of income sources, and separate the section of the tax base and delegate locally. The whole of discussion tries to demonstrate the validity of the proposed solutions. This leads to practical recommendations on the selected issues of the local finance system in Poland.